Microscopic and molecular diagnoses of Giardia duodenalis in pet animals in Babylon Province, Iraq - Shurook R. Idan; Mohammad H. Al-Hasnawy (Veterinary World, 2023)
Background and Aim: The breeding of pet animals, especially dogs and cats, in Iraq has increased recently. However, no epidemiological or molecular data exist regarding Giardia duodenalis infection in pet animals, particularly in Babylon Province. Therefore, this study aimed to detect G. duodenalis and its genotypes in pets using microscopic and molecular techniques.